Autodisplay of the LaiSSB protein on LPS-free E-coli for the diagnosis of Sjogren's syndrome - Yoo, Gu; Dilkaute, Carina; Bong, Ji-Hong; Song, Hyun-Woo; Lee, Misu; Kang, Min-Jung; Jose, Joachim; Pyun, Jae-Chul (ELSEVIER SCIENCE INC, 2017)
The objective of this study was to present an immunoassay for the diaghosis of Sjogren's syndrome based on the auto displayed La/SSB protein on the outer membrane of intact E. coil (strain UT-5600) and LPS-free E. coil (ClearColi (TM)). As the first step, an autodisplay vector (pCK002)was transfected into intact E. coli and LPS-free E. coli for comparison of efficiency of autdisplay of La/SSB. The Maximal level of La/SSB expression was estimated to be similar for LPS-free E. coli and intact E. coli at different optimal induction periods. Intact E. coli was found to grow twofold faster than LPS-free E. coli, and the maximal level of expression for LPS-free E. coil was obtained with a longer induction period. When the zeta potential was measured, both intact E. coli and LPS-free E. coli showed negative values, and the autodisplay of negatively charged La/SSB protein (pI < 7) on the outer membrane of intact E. coil and LPS-free E. coli resulted in a slight change in zeta potential values. E. coli with autodisplayed La/SSB protein was used for an immunoassay of anti-La/SSB antibodies for the diagnosis of Sjogren's syndrome. The surface of E. coli with the autodisplayed antigen was modified with rabbit serum and papain to prevent false positive signals because of nonspecific binding of unrelated antibodies from human serum. LPS-free E. coli With autodisplayed La/SSB protein yielded sensitivity and selectivity of 81.6% and 78.6%, respectively. The Bland-Altman test showed that the immunoassays based on LPS-free E. coli and intact E. coli with autodisplayed La/SSB protein were statistically equivalent to a clinical immunoassay for detection of anti-La/SSB antibodies (confidence coefficient 95%). (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Z-DOMAINS; SURFACE DISPLAY; E. COLI; OUTER-MEMBRANE; BACTERIAL LIPOPOLYSACCHARIDES; RECOMBINANT PROTEINS; MEDICAL DIAGNOSIS; SPR BIOSENSOR; HUMAN SERUM; IMMUNOASSAY